Provocation problems in Lebanese Christian brothers schools: staff and teachers insights - Spanioli, Edouard (Beirut Middle East University, 2014)
The purpose of the research was to study staff and teachers insights and behaviors towards the provocation problem, existing school rules and processes, and training-session needs in a group of Lebanese Christian Brothers schools. The inquiry methodology and the key informant approach were used. Data were collected using two questionnaires in English and French. The content validity of the instruments was established by a preliminary pilot study. Copies of written school rules were collected. The questionnaires included many open-ended and closed-ended items. Data analysis involved thematic analysis and descriptive statistical analysis. The data indicated that teachers showed a high level of awareness of what behaviors constitute provocation. Most teachers recognize the existence of provocation problems in their school, but do not regard them as very serious ones. Most of the selected schools in the sample did not have any specific provocation rules but did have regulations addressing provocation-related issues. Regarding staff and teachers views towards teachers duties in dealing with the problem, almost all staff and teachers agreed that teachers play an important role in preventing provocation and that they must intervene whenever they see provocation happening. Staff and teachers generally believed that they need a training session to deal with provocation. A series of recommendations is presented including a proposed outline for a professional development training session on provocation.
: Mémoire
Keywords: Climat scolaire; Education religieuse; Les Attitudes et conceptions des enseignants; Religious education; Teachers attitudes and conceptions School Climate